Study of efficacy of using recycled waste concrete as fine aggregates in self compacting concrete - Charush (My University, 2013)
Self-Compacting Concrete (SCC) represents one of the biggest modern innovations in the construction field worldwide. Until now, on an international level, the number of constructions using SCC as a main material is limited. A self-compacting concrete (SCC) is the one that can be placed in the form and can go through obstructions by its own weight and without the need of vibration. Since its first development in Japan in 1988, SCC has gained wider acceptance in Japan, Europe and USA due to its inherent distinct advantages. SCC provides better quality especially in the members having reinforcement congestion or decreasing the permeability and improving durability of concrete”. In the present graduate thesis there is a thorough report on mechanical properties and the major attributes of the fresh and hardened concrete, as well as on the methods of production and the ingredients of the recycled materials. The primary study is to explore the acceptability of demolished concrete waste aggregate to make self compacting concrete of high strength and desirable properties. It addresses experiments on various mixes of self compacting concrete – one with fresh coarse and fine aggregates, while the others with replacement of 25%, 50 %, 75% and 100% recycled fine aggregates. Results showed the fresh, hardened and durability properties of all the concrete mixes were comparable. The compressive strength of all the concrete mixes was measured at the age of 7 and 28 days.
Master of Engineering-Structural Engineering, Dissertation
Keywords: Recycled; Mechanical; Self Compacting Concrete; Waste Aggregates